Hexachlorocyclohexane and DDT in marine organisms from the Bering and the Okhotsk Seas - Vasily Yu. Tsygankov (Известия ТИНРО, 2014)
Organochlorine pesticides (HCHs and DDT) are harmful and toxic substances affected biota. HCHs and DDT are still used as pesticides in the Southern Hemisphere and from there can reach the North Pacific due to atmospheric transfer. Isomers of HCH and DDT and their metabolites were detected in organs of some marine mammals ( Eschrichtius robustus, Odobenus rosmarus divergens ) from the Bering Sea; the maximum concentration was found in the walrus liver (90263 ng/g lipids). To trace these pollutants spreading in the Okhotsk Sea, the seabirds (Pacific gull Larus schistisagus, crested auklet Aethia cristatella, auklet crumb Aethia pusilla, northern fulmar Fulmarus glacialis, and grey petrel Oceanodroma furcata ) and fishes (pink salmon Oncorhynchus gorbusсha and chum salmon Oncorhynchus keta ) were sampled; the pesticides concentration in the birds tissues ranges from 29 ng/g lipids in plume of the fulmar to 16095 ng/g lipids in plume and skin of the auklet and in the salmons tissues - from 220-330 ng/g lipids for the pink salmon to 550-790 ng/g lipids for the chum salmon (both fish species were caught at Kuril Islands).